Reactive Oxygen Species (ROS) in Living Cells 2018
DOI: 10.5772/intechopen.71465
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecules Oxidation by Hydrogen Peroxide and Singlet Oxygen

Abstract: Hydrogen peroxide (H 2 O 2) and singlet oxygen (1 O 2) are important reactive oxygen species (ROS) for biological and medicinal fields. Oxidation processes of chemical materials by molecular oxygen are important H 2 O 2 source, whereas photochemical reaction is important for 1 O 2 production. Reactivity and biomolecule damage by these ROS depend on the surrounding conditions and targeting molecules. In this chapter, production mechanisms of H 2 O 2 and 1 O 2 , biomolecule oxidation by these ROS, their detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 129 publications
(200 reference statements)
0
4
0
Order By: Relevance
“…Compared to the other ROS, H 2 O 2 is the most stable and the least reactive ROS and can easily pass through the membrane, making it an appropriate signalling molecule. The effect of H 2 O 2 is dose-dependent and exerts a diverse range of effects, from improving cell viability to cell death 50 , 51 . Here we found out that the CAP exposure produced a substantial concentration of H 2 O 2 with rising trends over the time course of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the other ROS, H 2 O 2 is the most stable and the least reactive ROS and can easily pass through the membrane, making it an appropriate signalling molecule. The effect of H 2 O 2 is dose-dependent and exerts a diverse range of effects, from improving cell viability to cell death 50 , 51 . Here we found out that the CAP exposure produced a substantial concentration of H 2 O 2 with rising trends over the time course of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In biological systems, singlet oxygen ( 1 O 2 ) is mostly generated by photosensitization reactions, since 1 O 2 is an excited state of O 2 , which needs the energy transmitted by the light to reach this state (50). Even VL possesses enough energy to promote the formation of 1 O 2 (51). It is the primary oxidant of the photo‐oxidative stress and has a strong oxidant potential that can alter proteins, lipids, and DNA (49).…”
Section: Discussionmentioning
confidence: 99%
“…Among 2-arylbenzofuran isolated in this study, 2 and 6, which have a p-quinone structure in the B ring, showed absorption in the visible range, while 10 did not have an absorption peak in the visible range. The key difference amongst these compounds is the identity of ring B: p-benzoquinone in 2 and 6, and resorcinol in 10. p-benzoquinone is readily formed by the autoxidation of hydroquinone (Wiley 2012;Kazutaka 2018). We therefore propose that the p-benzoquinone rings of 2 and 6 are formed via autoxidation of hydroquinone-containing precursors.…”
Section: Uv-vis Analysis Of 2-arylbenzofuransmentioning
confidence: 97%